PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN DENGAN MENGGUNAKAN MEDIA KARTU KATA - Eminarni, Eminarni (Jurnal Likhitaprajna, 2018)
This study aims to improve the initial reading skills by using word card media for grade 1 students at SD Negeri I Sidogiri. This type of research is a collaborative classroom action research conducted in two cycles. The results of the study show that learning to read the beginning by using word card media can improve the reading skills of grade 1 students at SD Negeri I Sidogiri. Reading skills in pre-action amounted to 62.74 and the completeness was 48%, in the first cycle it increased to 69.9 with completeness 74%, the increase in the second cycle was 76.7 with completeness of 90%. In this action the students' reading skills with pronunciation, intonation and reading comprehension increased until they reached the specified completeness criteria, namely with the class 70 average and 80% grade completeness. In the first cycle used a word card with a size of 13 x 6 cm and each word with one color, in the second cycle a word card that was larger than 18 x 6 cm was used and each word contained an expression of words separated by different colors.Keywords: reading skills, media of learning, word card